College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 1, Equations and Graphs - Section 1.4 - Solving Quadratic Equations - 1.4 Exercises - Page 123: 52



Work Step by Step

First we cross-multiply: $S= \displaystyle \frac{n(n+1)}{2}$ $2S=n^{2}+n$ $n^{2}+n-2S=0$ Now we use the quadratic formula: $n=\displaystyle \frac{-1\pm\sqrt{(1)^{2}-4(1)(-2S)}}{2(1)}=\frac{-1\pm\sqrt{1+8S}}{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.